Modifikasi Perkerasan Apron Pada Bandar Udara Juwata Tarakan Menggunakan Pelat Berongga Dua Arah - Noerman Adi Prasetya (Borneo Engineering : Jurnal Teknik Sipil, 2023)
AbstractThe purpose of this research is to develop a two-way hollow slab as an alternative pavement for the development of the Juwata Airport apron, Tarakan City, while the research method to be carried out is to modify the existing apron pavement structure with the new type of structure offered, then the results of the new design will be compared with the existing design. The results obtained are i) the number of surface reinforcement to withstand the bending of the 2-way cavity slab structure asan apron pavement is relatively the same as conventional pavement, but for the slab system that is offered the placement of reinforcement is 2 layers, ii) the total volume of concrete usage is reduced by 23.52 %, iii) the volume of use of reinforcing iron increased by 100%. This research is expected to be information and input for structural planners in designing buildings made of reinforced concrete, especially in rigid pavement structures, then provide an alternative type of apron structure for the future development of Juwata Airport.Keywords: Rigid Pavement, Apron, Rigid Pavement Restraints                                                                                   AbstrakTujuan dari penelitian ini adalah menemukembangkan pelat berongga dua arah sebagai alternatif perkerasan untuk pengembangan  apron Bandar Udara Juwata Kota Tarakan, adapun metode penelitian yang akan dilaksanakan adalah dengan memodifikasi struktur perkerasan apron eksisting dengan jenis struktur baru yang ditawarkan, lalu hasil dari desain baru tersebut akan dikomparasikan dengan desain eksisting. Hasil yang diperoleh adalah i) jumlah tulangan permukaan untuk menahan lentur struktur pelat rongga 2 arah sebagai perkerasan apron relatif sama dengan perkerasan konvensional, akan tetapi untuk sistem pelat yang ditawarkan penempatan tulangan menjadi 2 lapis, ii) jumlah volume pemakaian beton berkurang sebesar 23,52%, iii) jumlah volume pemakaian besi tulangan meningkat 100%.  Penelitian ini diharapkan dapat menjadi informasi dan masukkan kepada perencana struktur dalam mendesain bangunan berbahan beton bertulang, khususnya pada struktur perkerasan kaku, lalu memberikan alternatif jenis struktur apron untuk pengembangan Bandar Udara Juwata kedepannya.Keywords: Perkerasan Kaku, Apron, Tumpuan Perkerasan Kaku